Type 2 Inflammation and Upper Gastrointestinal Symptom Traits in the Clinical Course of Chronic Cough: A Real-World Cough Clinic Study - Keima Ito; Yoshihiro Kanemitsu; Yuki Amakusa; Tatsuro Suzuki; Ziwen Ma; Yuta Mori; Kensuke Fukumitsu; Satoshi Fukuda; Takehiro Uemura; Tomoko Tajiri; Hirotsugu Ohkubo; Tetsuya Oguri; et al. (ERJ Open Research, 2026)
Background Type 2 inflammation and upper gastrointestinal symptom traits are common in chronic cough but their relationship with cough resolution in practice remains unclear. Methods This retrospective study included 256 patients with chronic cough followed up for ≥3 months between 2012 and 2020. Type 2 inflammation was defined as peripheral blood eosinophils ≥300 cells/μL, FeNO ≥25 ppb, or serum total IgE ≥100 IU·mL −1 . Reflux symptoms (RS) and dysmotility symptoms (DS) were assessed using the modified Frequency Scale for the Symptoms of GERD. Severe RS was defined as RS >7, and DS >1 was considered a dysmotility-related symptom trait. Time to physician-assessed cough resolution was evaluated using Kaplan–Meier analysis and Cox proportional hazards models. Results Patients with severe RS had a longer median time to cough resolution than those with non-severe RS (3.8 versus 2.0 months) and a higher 12-month rate of unresolved cough (20.3% versus 16.3%; p